Gastroprotective effects (in rodents) of a flavonoid rich fraction obtained from Syngonanthus macrolepsis - Batista, Leonia Maria; Albino de Almeida, Ana Beatriz; Morais Lima, Gedson Rodrigues de; Falcao, Heloina de Sousa; Magri, Luciana de Pietro; Luiz-Ferreira, Anderson; Santos, Lourdes Campaner dos [UNESP]; Hiruma-Lima, Clelia Akiko [UNESP]; Vilegas, Wagner [UNESP]; Monteiro Souza Brito, Alba Regina (Wiley-Blackwell, 2014)
Objectives: Syngonanthus macrolepis, popularly known in Brazil as sempre-vivas', is a plant from the family Eriocaulaceae, it is found in the states of Minas Gerais and Bahia. The species contains a variety of constituents, including flavonoids with gastroprotective effect. In this work, a flavonoid-rich fraction (Sm-FRF) obtained from scapes of S.macrolepis was investigated for preventing gastric ulceration in mice and rats.MethodsThe activity was evaluated in models of induced gastric ulcer (absolute ethanol, stress, non-steroidal anti-inflammatory drugs and pylorus ligation). The cytoprotective mechanisms of the Sm-FRF in relation to sulfhydryl (SH) groups, nitric oxide (NO) and antioxidant enzymes were also evaluated.Key findingsThe Sm-FRF (100mg/kg, p.o.) significantly reduced gastric injury in all models, and did not alter gastric juice parameters after pylorus ligation.ConclusionsThe results indicate significant gastroprotective activity for the Sm-FRF, which probably involves the participation of both SH groups and the antioxidant system. Both are integral parts of the gastrointestinal mucosa's cytoprotective mechanisms against aggressive factors.
Keywords: Eriocaulaceae; flavonoid; gastroprotective activity; medicinal plants; Syngonanthus macrolepsis